1988
DOI: 10.1037/0022-0663.80.4.480
|View full text |Cite
|
Sign up to set email alerts
|

Language comprehension in learning disabled children who perform poorly on memory span tests.

Abstract: In this article, we report three studies of language comprehension skills in 9-and 10-year-old learning disabled (LD) children who have extreme difficulties retaining brief sequences of verbal information. In all studies, the performance of this subgroup of LD children is contrasted with other LD subjects who perform normally on memory span tests and with normally achieving subjects. In Experiment 1 we showed that although children in the target subgroup had difficulties remembering the specific words and word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
(28 reference statements)
0
5
0
1
Order By: Relevance
“…These difficulties are likely to affect readers’ ability to encode printed words, to manipulate the word structures and to analyze the meaning of morphologically complex words. Moreover, adolescents with dyslexia have short-term verbal memory (Torgesen et al, 1987 ; Wijsman et al, 2000 ) and long-term working memory difficulties (Hulme, 1981 ) that cause problems in creating word representations in memory and retrieving them from memory. Other studies reported that the manifestations of cognitive deficits can change over the life span (Bruck, 1990 ; Nation & Snowling, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…These difficulties are likely to affect readers’ ability to encode printed words, to manipulate the word structures and to analyze the meaning of morphologically complex words. Moreover, adolescents with dyslexia have short-term verbal memory (Torgesen et al, 1987 ; Wijsman et al, 2000 ) and long-term working memory difficulties (Hulme, 1981 ) that cause problems in creating word representations in memory and retrieving them from memory. Other studies reported that the manifestations of cognitive deficits can change over the life span (Bruck, 1990 ; Nation & Snowling, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Asking subjects to describe stimuli in their own words is a common approach to assessing gist in research on memory and comprehension (e.g. Adams et al, 1990;Langer et al, 1987;Torgesen et al, 1988). However, in this research, memorial limitations were not an issue since each item was presented verbatim at the time of gist assessment.…”
mentioning
confidence: 98%
“…In contrast, several recent studies (e.g., Ceci et aL, 1980;Torgesen et al, 1987;Vellutino and Scanlon, 1985, 1987a, 1987b) have implicated verbal coding as a stable processing disability in various subgroups (e.g., reading) of LD children. Support for the verbal coding dificit hypothesis is most evident, however, in Vellutino's work (see Vellutino, 1977;Scanlon, 1982, 1987a).…”
Section: Modality-specific Processingmentioning
confidence: 81%